Production Practices, Constraints and Performance in Traditional Chicken Breeding in Chad - Issa , A.Y.; Mopate, L.Y.; Ayssiwede, S.B.; Missohou, A. (International Journal of Poultry Science, 2013)
The objective of this work was to characterize the production of chickens and technical performance of family poultry farms in the Departments of Hadjer Lamis in the Sahel zone and West Tandjilé in the Sudanian zone. The crosscutting and retrospective survey covered 16 villages and 233 farmers randomly selected. The investigated Livestock was made up of 5208 birds. Poultry farmers are mainly farmers (86.7%), with an average age of 40.7 ± 14.9 years practice poultry farming as a secondary activity. They are mostly men (71.2%), illiterate (51.5%) and especially married (91.8%). The majority of men (70.4%) reported being owners of the poultry yards. Dominant types of henhouses are huts (45.1%) and rudimentary livestock structures (35.5%). Feed distributed to poultry are mainly cereals (77.7%) served on the ground (60.9%), 2 times a day by 96.6% of poultry farmers. Drinking water is served in old utensils (47.2%), broken jars or pottery (39.1%) and wooden containers (13.7%). Medical prophylaxis is non-existent; farmers make use of traditional care in case of bird disease. Newcastle disease and predation are the main causes of mortality in chicken breeding. The size of the poultry yards is 16.8 ± 19.9 chickens for a hens / rooster sex ratio of about 2.0. The age at first egg is 5.6 ± 1.31 months. The number of broods per annum is 3.57 ± 0.92, with 11.56 ± 2.23 eggs / egg-laying. The average hatching rate is about 87% and chick survival to weaning 74%. Production is mainly destined for sale (87.6%). With 22.68 ± 11.32 individuals sold per annum at an average price of 2270 FCFA per chicken, earnings are 51.529 CFA/annum per producer. The average number of chickens consumed is 6.99 ± 7.65 heads per annum. Decisions to sell chickens are made especially by men (60.5%), but only women have ensured the sale at the markets. No significant difference was observed between the two Departments at the socio-economic level and reproductive parameters of the birds, probably due to the similarity of practices implemented.